Fatty Acid and Alkenil Glycoside from the Fruits of Mengkudu (Morinda citrifolia Linn) - Ferlinahayati Ferlinahayati; Rizdha Apriyaty; Eliza Eliza (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2016)
Two compounds were isolated from methanol extract of mengkudu fruit (Morinda.citrifolia Linn). The extraction was conducted by maceration, while separation and purification using several chromatographic techniques. The compound structures were determined by spectral data including IR, 1H-NMR and GC-MS. Compound 1 was a mixture of 7 fatty acids with hexadecanoic acid as a primarily, meanwhile compound 2 was a mixture of an alkenyl glycoside with an aromatic.Keywords: Morinda citrifolia, asam lemak, alkenil glikosida(Indonesian) Dua senyawa telah diisolasi dari ekstrak metanol buah mengkudu (Morinda citrifolia Linn). Ekstraksi dilakukan dengan cara maserasi yang dilanjutkan dengan pemisahan dan pemurnian dengan menggunakan berbagai teknik kromatografi. Struktur senyawa ditentukan berdasarkan data-data spektroskopi yaitu IR, 1H-NMR dan GC-MS. Senyawa 1 merupakan campuran dari tujuh asam lemak dengan kandungan utama asam heksadekanoat sedangkan senyawa 2 merupakan campuran alkenil glikosida dengan senyawa aromatik.Kata kunci: Morinda citrifolia, asam lemak, alkenil glikosida